Hubungan Gangguan Fungsi Kognitif dengan Hipertensi Menggunakan Montreal Cognitive Assessment Versi Indonesia (Moca-Ina) - Enny Lestari; Melfi Riqqah; Ilhami Romus (Fakultas Kedokteran Universitas Riau, 2017)
High blood pressure associated with a reduction of cognitive function in young adults and older age. One of cognitiveimpairment examination is Montreal Cognitive Assessment (MoCA). The aim of this study is to determine the correlationbetween impaired cognitive function with hypertension by using MoCA–INA in the elderly people at Tresna WerdhaKhusnul Khotimah nursing home Pekanbaru. This research obtained the incidence of impaired cognitive function inelderly people at Tresna Werdha Khusnul Khotimah nursing home Pekanbaru as many as 28 subjects (90.3%).Hypertension in the elderly at Tresna Werdha Khusnul Khotimah nursing home Pekanbaru were 23 subjects consistof 6 subjects (19.35%) with controlled hypertension and 17 subjects (54.84%) with uncontrolled hypertension. Theresults of statistical test by using Fisher test obtained p value as big as 1.000 (p>0.05). This shows there is nosignificant correlation between impaired cognitive function with hypertension in the elderly people at Tresna WerdhaKhusnul Khotimah nursing home Pekanbaru.